The Sound Handbook. - Crook, Tim (Media practice., 2011)
""The Sound Handbook"" is an essential practice and theory guide that sets out the best methods in producing sound for multi-media and the academic theories that underpin the history and analysis of sound expression. ""The Sound Handbook"" teaches how qualitative sound can be produced for drama, documentary and journalism in radio, theatrical stage production, television and film, online, animation, videogames, and sound art installation. At the same time, the theoretical debates that constitute textual and contextual academic study of sound in these media platforms are explored. ""The Sound H.